Medicinal Plants Used for the Treatment of Tuberculosis by Bapedi Traditional Healers in Three Districts of the Limpopo Province, South Africa - Semenya, Sebua Silas (African Networks on Ethnomedicines, 2012)
The present study was aimed at documenting medicinal plants used for the treatment of tuberculosis (TB) by the Bapedi traditional healers in three districts of the Limpopo Province, South Africa. Fifty two traditional healers from 17 municipalities covering Capricorn, Sekhukhune and Waterberg districts were interviewed between January and July 2011. Twenty one medicinal plant species belonging to 20 genera and 18 families were documented. The majority (61.9%) are indigenous and the rest are exotics, found near homes as weeds or cultivated in home gardens as ornamentals or food plants. Hyacinthaceae, Moraceae and Rutaceae families were the most represented families in terms of species numbers (9.5% each). Herbs and trees (38% each) constituted the largest proportion of the growth forms of the medicinal plants used. Tuberculosis remedies were mostly prepared from leaves (34%) followed by roots (21%). The therapeutic claims made on medicinal plants used to treat TB by the Bapedi traditional healers are well supported by literature, with 71.4% of the species having antimicrobial properties or have similar ethno medicinal uses in other countries. This study therefore, illustrates the importance of medicinal plants in the treatment and management of TB in the Limpopo Province, South Africa.